Application of a SEM-EDS-Based Automated Process Mineralogy Analyzing System on the Occurrence State of Silver in Copper Ore Flotation Tailings - Ligang WEN; Muxin JIA; Jianjun ZHAO; Qing WANG; Qiang FU (Yankuang ceshi)
The silver occurrence state and process mineralogical characteristics are critical to its beneficiation process and recovery indicators, which can be used for assisting in process development, plant design, and improvement of silver recovery. In order to define the occurrence state of silver in copper ore flotation tailings with low-grade Ag 41.96µg/g & Cu 0.44%, BGRIMM process mineralogy analyzing system (BPMA) with version 2.0 BPMA software, scanning electron microscopy (SEM) and energy dispersive X-ray spectrometer (EDS) were applied to investigate the copper mineralogical characteristics and silver occurrence state of the flotation tailings. The copper minerals in the tailings are mainly fine-grained and poorly liberated copper sulfide minerals; the silver mainly occurs as independent silver minerals, with high liberation and non-uniform grain size. The analytical results show that the BPMA & SEM-EDS in situ analysis method can serve as a technical reference for the study of the occurrence state and process mineralogy of rare precious metal elements. The BRIEF REPORT is available for this paper at http://www.ykcs.ac.cn/en/article/doi/10.15898/j.ykcs.202310250165.